SIGNAGE YANG INFORMATIF DAN INTERAKTIF PADA THE HERITAGE PALACE KOTA SURAKARTA JAWA TENGAH - Hanifunisa, Aulia; Swasty, Wirania (Institut Bisnis dan Teknologi Indonesia, 2020)
The Heritage Palace is located in Surakarta City of Central Java which formerly was the sugar factory that is currently used as a tourist attraction. However, this place has the problem of lacking its informative and interactive signage, less by the branding of the tourist spots, and less proper in material selection. The data collection used were the literature study, observation, interviews and questionnaires, using comparison matrix as data analysis method. The concept of the design takes the modern and old heritage concept using a font that matches the clear language and adds pictogram. The purpose of this design is to provide informative and interactive information using signage ang interactive media that is useful to help visitors get information when they visit the tourist site